The Parent University Program: Factors predicting change in responsive parenting behaviors. (October 2017) - Liggett-Creel, Kyla; Barth, Richard P.; Mayden, Bronwyn; Pitts, Britney E.
Abstract: Few evidence-based parenting programs exist for children under the age of three and even fewer have been rigorously evaluated in comparison to parenting programs for older children. The Parent University Program (PUP), was developed to serve parents with children birth through three who lived in southwest Baltimore. Parent-child dyads ( N = 86) participated in the parenting program with the goal of increasing responsive parenting skills. Participants of the PUP showed a significant increase in responsive parenting behaviors. Participants in this open trial study who completed pre-test, post-test, and follow-up assessments showed a significant change from clinical to non-clinical status after attending the PUP. Neither the type of facilitator nor the number of hours attended showed an association with changing parenting behaviors. The age of the child was associated with the change in responsive parenting. Parents of older children in the birth to three age range had higher scores at pre-test and showed less change over time. The results of this study suggest that the Parent University Program was associated with positive change in responsive parenting behaviors for parents with children birth through three years of age. Highlights: The PUP program was developed to increase responsive parenting skills. Participants who showed leadership were brought back as peer leaders. The PUP participants showed improvements in responsive parenting behaviors. Facilitator type, social worker or peer, was not associated with change in parenting. Number of hours attended in the program was not associated with change in parenting.